Tony Oursler - I/O underflow - Oursler, Tony 1957-; Serrano, Ester (Stichting de Oude Kerk, 2015)
Multimedia and installation artist Tony Oursler was commissioned by the Oude Kerk in Amsterdam to develop new works for a solo exhibition. Using digitally produced video performances, he hacked the church with works that expose and call into question the relation between humans and computers. The projected installations confronted visitors with their own presuppositions about identity, privacy, and reality. Photographs of the works and dialogues from the video performances are collected in this book, which also features an introduction to Ourslers earlier work, an in-depth interview, and reflections on the new works, all illustrated with images from the artists own archives